In-situ monitoring of oil emulsion fouling in ultrafiltration via electrical impedance spectroscopy (EIS): influence of surfactant - Tian, Ju (2022)
Some inconsistencies were found in the literature on the effect of surfactant type on membrane fouling by surfactant-stabilized oil emulsions. For instance, a recent study showed that the fouling trends revealed by optical coherence tomography (OCT) were incongruent with the flux decline trends. This study was targeted at providing more mechanistic insights on the evolution of the distinct membrane layers (namely, diffusion polarization, membrane skin and membrane microporous substrate layers) via electrical impedance spectroscopy (EIS). The three surfactants investigated were cationic cetyltrimethylammonium bromide (CTAB), anionic sodium dodecyl sulphate (SDS) and non-ionic Tween 20, the oil was hexadecane, and the ultrafiltration membrane was polyethersulfone (PES). The Tween 20-stabilized oil emulsions exhibited a greater flux decline than that of SDS, which agreed well with the relative shifts of the Nyquist plots and increase in conductance with time. Interestingly, the CTAB-stabilized oil emulsions exhibited a unique flux decline trend, in which the flux decline was the least in the initial 0.5 h then the worst beyond 0.75 h. Despite the negligible flux decline initially, EIS results indicated significant shifts of the Nyquist plots and increase of the conductance with time, which was tied to the extensive adsorption of CTAB. As filtration progressed beyond 0.5 h, the conductance and capacitance of the membrane skin layer in the case of CTAB-stabilized oil emulsions became respectively higher and lower than that in the case of CTAB alone, signifying that the deposition of oil emulsions had become more dominant than that of surfactants. Therefore, this study provided clear evidence that the surfactant oppositely charged to the membrane (i.e., CTAB) adsorbed extensively initially to give negligible flux decline, which was not the case for the surfactants that were similarly negatively charged like the membrane. This only lasted for 0.5 h beyond which fouling became pronounced per dictated by DLVO interaction energy.